Information technology concepts in the Journal of the American Society for Information Science and Technology (JASIS&T) articles and library and information a relational a alysis - Baselonia, Alma S. (2007)
Journals play an important role in helping people become informed by publishing the recent information or practices reflecting what is going on in a given field of study. It is said that journals emanating from learned and professional societies are usually considered as the ones most likely to carry articles of authoritative, fundamental-discovery type in their specific subject fields. Is in this light that this study examined the contents of the 1996-2006 issues of the Journal of the American Society for Information Science and Technology (JASIS&T). The study utilized relational analysis to satisfy its objectives. A total of 812 articles that discussed information technology (IT) per se or its applications and are related to library and information science (LIS) were included in relational analysis. Relationships between concepts were determined and measured using Pearson's Correlation and presented in graphical forms (maps). The subject or area of librarianship of each article was classified using the ""ASIS Thesaurus of Information Science,"" 2nd edition.